1-Tetradecylindoline-2,3-dione - Mamari, K.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title N-alkyl isatin, C(22)H(33)NO(2), the isatin moiety is planar (r.m.s. deviation = 0.03 angstrom). The tetradecyl substituent has all torsion angles in an antiperiplanar conformation.